An overview of the minimum wrestling weight procedures used in American scholastic and collegiate wrestling - Could this be a model for FILA? - Curby, D. (FILA Advanced school for coaches - proceedings 2013, 2013)
The health-related concerns regarding drastic weight loss measures to make weight in wrestling have been well documented. The American College of Sports Medicine (ACSM) has long been on record for the adoption of a system to discourage these practices. They published their first position stand on weight loss in wrestlers in 1977. Following the deaths of three college wrestlers in 1997, the National Collegiate Athletic Association (NCAA) moved quickly to adopt a weight control plan that included the establishment of a minimal weight class for each individual. All state athletic associations were required to have weight control plans in place by 2004. This paper summarizes the methods that are currently utilized in the USA in the administration of these weight control programs, with an eye towards FILA and its possible adoption of a similar program